A study of the evolution of the third COVID‐19 pandemic wave in the Athens metropolitan area, Greece, through two cross‐sectional seroepidemiological surveys: March, June 2021. Issue 4 (4th December 2021) - Maltezou, Helena C.; Krumbholz, Bettina; Mavrouli, Maria; Tseroni, Maria; Gamaletsou, Maria N.; Botsa, Evanthia; Anastassopoulou, Cleo; Gikas, Aristofanis; Fournarakou, Evanthia; Kavieri, Maria; Koureli, Aikaterini; Mandilara, Dionysia; et al.
Abstract: We studied the third coronavirus disease 2019 (COVID‐19) pandemic wave in Athens metropolitan area (3 738 901 inhabitants) through two seroepidemiological surveys. Persons presenting in 12 healthcare facilities across Athens in March and June 2021 were studied (764 and 901, respectively). Immunoglobulin G antibodies against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike protein were measured by a chemiluminescent microparticle immunoassay. In March the seroprevalence rate was 11.6%, meaning that 435 208 residents of Athens had evidence of immunity. The respective values in June were 55.7% and 2 082 568 residents. The highest seroprevalence rates attributed to SARS‐CoV‐2 infection were recorded in persons <18 years (16.3% in March and 31.6% in June), while immunity was mainly vaccine‐induced in persons 18–64 years and >65 years. Infection‐attributed immunity also increased in older‐age groups. Wide ranges in seroprevalence rates were noted across areas in March and June. The highest seroprevalence rates were recorded in Piraeus (47.2%) and West Attica (37.5%). However, the highest increase (>5 times) occurred in Piraeus and the South Section of Athens, which are among the most densely populated areas in Athens. In both study periods, history of COVID‐19 or febrile episode, and having a cohabitant with COVID‐19 were associated with increased risk for seropositivity among unvaccinated persons ( p values <0.001 for all). Residing in Piraeus, the South Section or West Attica was associated with increased risk for seropositivity in June ( p values <0.001). Wide heterogeneity in seroprevalence rates was found across areas in Athens, which is mainly attributed to population density. The impact of population mobility and socioeconomic status should be explored.